HALAL CERTIFICATION AND ITS IMPLICATIONS ON PROCESSED FOOD PRODUCTS IN MSMEs: SERTIFIKASI HALAL DAN IMPLIKASINYA TERHADAP PRODUK PANGAN OLAHAN PADA UMKM - Mutiah Khaira Sihotang (UPMI Proceeding Series, 2023)
Study This aim For know How implications halal certification for product processed MSME food in Medan City. Type of research This qualitative descriptive based on philosophy _ postpositivism or interpretative . Data collection techniques were carried out in a way triangulation , data analysis in nature inductive , and outcome study qualitative more emphasize meaning than generalization . Study This including type studies field and library . Technique used For collect data ie with method observation , interviews , documentation and triangulation . Respondents . Observation in study This carried out at MUI, LPPOM MUI and Medan city MSME actors . Research results This state that Implications product certified halal in the city of Medan provides opportunity pasa for MSMEs , no _ only For in city but also capable reach export import . This thing make government emit policy new that every MSME actors must own products that are halal certified . By direct policy This implications to it opened field new in the field of halal auditor.